Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
[tex]x^2- 40 = 0\ \ \ \Leftrightarrow\ \ \ x^2-(2 \sqrt{10} )^2=0\\\\\ \ \ \Leftrightarrow\ \ \ (x-2 \sqrt{10} )(x+2 \sqrt{10} =0\\\\ \ \ \Leftrightarrow\ \ \ x=2 \sqrt{10} \ \ \ \ \ or\ \ \ \ \ x=-2 \sqrt{10[/tex]
Answer:
Given the quadratic equation: [tex]x^2-40=0[/tex]
Addition property of equality states that you add the same number to both sides of an equation.
Step 1.
[tex]x^2-40=0[/tex]
Add 40 to both sides of an equation:
[tex]x^2-40+40=0+40[/tex]
Simplify:
[tex]x^2=40[/tex] ......[1]
Step 2.
Take square root both sides in equation [1]; we have
[tex]\sqrt{x^2} =\sqrt{40}[/tex]
Simplify:
[tex]x=\pm \sqrt{40} =\pm 2\sqrt{5}[/tex]
Hence, the roots for the given equation is x = [tex]+2\sqrt{5}[/tex] , [tex]-2\sqrt{5}[/tex] .
Therefore, for solving the quadratic equation the first step is; Adding 40 to both sides of an equation.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.